Ten lectures on the basics of cognitive grammar - Langacker, Ronald W. (Distinguished Lectures in Cognitive Linguistics Ser., 2017)
These lectures provide a basic introduction to the linguistic theory known as Cognitive Grammar. It is argued that a conceptualist semantics, well motivated in its own terms, provides the basis for a symbolic view of grammar. Consisting in the structuring and symbolization of conceptual content, grammar is inherently meaningful, and basic grammatical notions have conceptual characterizations. An account is given of grammatical categories, markings, and constructions. A number of central topics are examined in detail, including subjects, possessives, locatives, voice, and impersonals.